Guest Editorial: Grid‐forming converters placement and utilisation to enhance transmission and distribution performances under high penetration of inverter‐based resources. Issue 2 (5th January 2023) - Babak, Badrzadeh; Julia, Matevosyan; Zia, Emin; Chao, Lu
Abstract: Power systems around the world are rapidly transitioning to much higher shares of inverter‐based resources (IBRs) with few synchronous generators remaining online. IBRs and synchronous generators have fundamentally different dynamic performance characteristics resulting in a difference in the overall power system dynamic performance. IBRs are generally more flexible and controllable than synchronous generators; however, at the same time they exhibit significantly more complex control systems. Furthermore, new and emerging capabilities are being developed progressively and in particular the so‐called grid‐forming inverters (GFM). GFM offer several new capabilities not previously possible with conventional grid‐following inverters (GFL). However, they are not well understood currently when applied in a mega scale and moving forward when they will likely take over the role synchronous generators have been performing for several decades as the workhorse of system security support. Key questions currently in the technical community include the extent to which GFM shall be similar or different to each of the synchronous machines and conventional GFL, and how various control strategies can assist in maximising the grid support capabilities sought and minimise or ideally eliminate any adverse impacts. The objective of this special issue is to provide insights into some of these unknowns.